QUANTITATIVE DISTRIBUTION OF BENTHOS IN THE EASTERN BERING SEA (Kolichestvennoe Raspredelenie Bentosa V Vostochnoi Chasti Beringova Morya) - Neiman,A. A. (1968)
In August-September benthos sampling on the shelf and the upper portion of the slope was carried out in the eastern part of the Bering Sea. Altogether, 104 dredge stations were occupied at depths from 20 to 500m. The mean benthos biomass in this region makes up 74.4g/sq. m, the main part consisting of bivalves and echinoderms. Qualitatively, the benthos of the investigated area can be divided into two complexes; low-arctic and boreal ones. Low-arctic complex achieves its greatest development in the northwestern part of the area investigated where it stretches from the shore to the isobath of 100m, while in the southeastern part it is situated in the narrow band at the depth of 50 to 70m. The remaining area of the shelf and upper horizons of the slope are occupied by boreal fauna. Low-arctic complex is characterized by Macoma calcarea and Ophiura sarsi, while the boreal one is characterized by Echinarachnius parma and Yoldia traciaeformis. (Author) Trans. of Zoologicheskii Zhurnal (USSR) v39 n9 p1281-1292 1960, by M. Slessers.